The Fear of COVID-19 Familial Infection Scale: Development and Initial Psychometric Examination. (3rd April 2022) - Mayer, Yael; Etgar, Shir; Shiffman, Noga; Lurie, Ido
Abstract: The Fear of COVID-19 Familial Infection (FCFI) scale examines parents' fear levels of infecting their families with COVID-19. Principle component analysis and confirmatory factor analysis in a sample of parents ( N  = 582) revealed two factors: Fear of infecting others and Others' Fear of being infected by me.